Konstruksi sosial budaya dan nilai pendidikan karakter dalam novel The Lost Java karya Kun Geia - Doni Uji Windiatmoko; Nugraheni Eko Wardani; Kundharu Saddhono (Fakultas Bahasa dan Seni UNP, 2020)
The purpose of this study is to describe the educational background of the author who influenced the novel The Lost Java by Kun Geia. Describe the socio-cultural background of the community contained in the novel The Lost Java by Kun Geia. Describe the reader response to the novel The Lost Java by Kun Geia. Describe the value of character education contained in the novel The Lost Java by Kun Geia. This research uses descriptive qualitative method with content analysis or content analysis. Data collection techniques with in-depth reading and interviews. Data validity using triangulation techniques, namely theory triangulation and data source triangulation. Data analysis techniques with interactive analysis techniques. The results showed that the author's high educational background. The socio-cultural background contained in the novel shows the social systems. The response of readers from expert and general readers, states the novel The Lost Java excels in the central theme, manifold science fiction, and can be used as teaching material. In addition, nine values of character education were found.